Komunikasi Politik Pemenangan Pasangan Bobby-Surya dalam Membentuk Loyalitas Gen Z pada Pilkada 2024 - Abdi Verdiansyaf; Muhammad Husni Ritongan (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2025)
Pilkada has a very important role in determining the direction and leadership of a region in the modern democratic era. In addition to serving as a formal process for electing leaders, elections are also a venue for influencing and shaping public opinion. In the context of modern democracy, political communication plays an important role in influencing public opinion and building relationships between prospective leaders and voters. This research aims to analyze how the political communication of the winning pair Bobby-Surya in winning the 2024 Pilkada and how the political communication of their winners in shaping Gen Z loyalty in the 2024 Pilkada. The research method used is qualitative with a case study approach, which involves interviews with members of the winning team. The results of the study show that the Bobby-Surya pair implemented an integrated communication strategy, combining conventional and digital approaches. Through the use of social media, engaging content, as well as collaboration with influencers, they managed to attract attention and build active engagement among Gen Z. In addition, value-based campaigns and transparency contributed to the formation of young voters' loyalty.